Pulls, pushes and entitlement failures in labor markets: does the state of development matter? - Sumon Kumar Bhaumik; Ralitza Dimova; Jeffrey B. Nugent (Institute for the Study of Labor (IZA), 2006)
This study adapts a relatively novel model of off-farm labor supply to the changing conditions of Bulgaria during the 1990s. The model's parameters are estimated separately for each of the three different waves of the Bulgarian Integrated Household Survey, each reflecting remarkably different environmental conditions. Both the parameter values and the changes therein from one survey year to another are explained and used to characterize the way different types of households allocate their labor between farm and off-farm activities. The results demonstrate that Bulgarian households display many of the same labor supply patterns, including entitlement failures, as have previously been observed only in very poor developing countries. As such, they have potentially important policy making implications.
Keywords: J2; P23; P36; O13; Q12; 330; off-farm labor supply; diversification; entitlement failures; transition economies; Bulgaria; institutional change